STRENGTHENING LEGAL CERTAINTY IN PUBLIC SERVICES: AN ANALYSIS OF GOOD GOVERNANCE PRINCIPLES IN GOVERNMENT ADMINISTRATION - Novran Harisa; Tao Wang (Institut Riset dan Pengembangan Indonesia, 2026)
This study aims to analyze the strengthening of legal certainty in public services through the implementation of good governance principles in government administration in Bengkulu. Legal certainty is important because public services must be delivered through clear procedures, transparent standards, accountable decisions, and equal treatment for all citizens. This study uses a normative-empirical legal research method with a qualitative descriptive approach. Normative analysis is applied to examine laws and regulations related to public services and government administration, while empirical analysis is used to understand public service practices, complaint mechanisms, and administrative supervision in Bengkulu. The findings show that good governance principles have contributed to strengthening legal certainty through service standards, transparency, accountability, responsiveness, public participation, complaint handling, and supervision by relevant institutions, including the Ombudsman. However, legal certainty has not been fully optimized because public service practices still face challenges such as procedural inconsistency, service delays, limited transparency, and uneven complaint resolution. This study concludes that legal certainty in public services depends not only on formal regulations, but also on consistent administrative implementation, professional public officials, effective supervision, and active public participation. Strengthening good governance in Bengkulu is therefore necessary to create public services that are fair, predictable, accountable, and responsive to citizens’ rights.